1996
DOI: 10.1007/bf00052670
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal risk factors for childhood brain tumors (Sweden)

Abstract: Childhood brain tumors (CBT) include a diversity of rare neoplasms of largely unknown etiology. To assess possible maternal and perinatal risk factors for CBT according to subtype, we carried out a nested (within Swedish birth-cohorts, 1973-89) case-control study, utilizing data from the nationwide Birth Registry. We ascertained incident brain tumor cases through linkage of the nationwide Birth and Cancer Registries and randomly selected five living controls from the former, matching each case on gender and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
5
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 46 publications
7
97
5
5
Order By: Relevance
“…As many comparisons were made, this may be a consequence of multiple hypothesis testing. However, several factors support a genuine association: the effect was more marked in younger children and was consistent across several types of infection, and other studies have reported evidence of an infective aetiology of these tumours (Linet et al, 1996;Linos et al, 1998;Fear et al, 2001;McNally et al, 2002).…”
Section: Main Findingsmentioning
confidence: 76%
See 3 more Smart Citations
“…As many comparisons were made, this may be a consequence of multiple hypothesis testing. However, several factors support a genuine association: the effect was more marked in younger children and was consistent across several types of infection, and other studies have reported evidence of an infective aetiology of these tumours (Linet et al, 1996;Linos et al, 1998;Fear et al, 2001;McNally et al, 2002).…”
Section: Main Findingsmentioning
confidence: 76%
“…No account could be taken of urban and rural areas within county districts, although they probably have different patterns of infection; we assumed that during pregnancy mothers were living in the area where their children were born, which is unlikely to be true for all; deaths from respiratory infections and influenza will reflect the standard of clinical care as well as the prevalence of infection in the community. In contrast to case -control studies (Bithell et al, 1973;Linet et al, 1996;McKinney et al, 1999;Fear et al, 2001) and some cohort studies (Adelstein and Donovan, 1972;Fedrick and Alberman, 1972), we did not have measures of individual exposure.…”
Section: Strengths and Weaknessesmentioning
confidence: 97%
See 2 more Smart Citations
“…Table 3 shows the results of the five previous prospective studies of cancer occurrence in twins (and our own). Of six heavily overlapping studies of childhood cancer from Sweden, (Forsberg and Källen, 1990;Zack et al, 1991;Cnattingius et al, 1995;Linet et al, 1996;Mogren et al, 1999;Rodvall et al, 1992), only one (Rodvall et al, 1992) reported a numerical risk for all childhood cancers in twins, that could therefore be included in a pooled analysis. Only one retrospective case-control study was identified (Savitz and Ananth, 1994) reporting a non-significantly increased odds ratio 1.5 (0.4-5.0).…”
Section: Resultsmentioning
confidence: 99%